PANDANGAN AL-GHAZALI TENTANG PENDIDIKAN MORAL - Ahmad Sahar (AN NUR: Jurnal Studi Islam, 2012)
This article is trying to expose critical and comparative thinking Al-Ghazali on moral education. Al-Ghazali is known as a Muslim theologian, expert education, and Sufi. The idea seems to inspire many subsequent thinkers, including thinking in the field of moral education. For Al- Ghazali education is effortless to tazkiyah al-nafs an attempt takhliyah al-nafs and tahliyah al- nafs. Takhliyah al-nafs was effortless adjustment through self-emptying of the despicable nature. While tahliyah al-nafs is decking themselves with moral and praise. Al-Ghazali thinking about moral education in line with the religious philosophy and Sufi is derived from revelation and reject ratio as the guiding principle of human ethical action.